Low seroprevalence of Coxiella burnetii in Boer goats in Missouri - Baker, Molly D (BioMed Central, 2014)
BACKGROUND: Goats are known reservoirs of Coxiella burnetii, the etiologic agent of Q fever. However, there has been very little research on the prevalence of C. burnetii exposure and risk in meat goats farmed in the US. Banked serum samples were secondarily tested for C. burnetii specific antibodies. FINDINGS: The animal and herd-level seroprevalence estimates for C. burnetii were 1.2% (3/249) and 4.2% (1/24) respectively. Within-herd seroprevalence ranged from 0% to 1.2%. CONCLUSIONS: This study indicates that seroprevalence of C. burnetii in Boer goats raised in Missouri was low, but it does not preclude the existence of a higher level of infection in Missouri’s meat goat herds. This result is inconclusive because this study was disadvantaged by the small number of individual animal and herds tested, which compromised the statistical power of this study to detect a possible higher seroprevalence of C. burnetii in this population, if present. More research is warranted to corroborate the preliminary findings reported here in order to determine the public health significance C. burnetii infection risks associated with contemporary goat production systems in the US.